Characterization of the complete chloroplast genome of Artemisia capillaris (Campanulales: Asteraceae Bercht), a unique economic plant to China - Peng Li; Guolun Jia (Mitochondrial DNA. Part B. Resources, 2019)
Artemisia capillaris is an endemic annual herb of Artemisia (Asteraceae Bercht) in China. The seedlings in early spring, removed old stems and impurities to dry, as a commonly used traditional Chinese medicine, has been listed in the Chinese Pharmacopoeia. The A. capillaris methanol (MeOH) extracts showed antioxidative activity and anticancer activity. The complete chloroplast (cp) genome was assembled by Illumina paired-end reads data. The circular cp genome is 151,074 bp in size, including a large single copy (LSC) region of 82,837 bp, a small single copy (SSC) region of 18,309 bp, and a pair of inverted repeat (IRs) regions of 24,964 bp. Besides, 11 genes possess a single intron, while another three genes ycf3, rps12, and clp have a couple of introns. The GC content of the entire A. capillaris cp genome, LSC, SSC, and IR regions are 37.58, 30.7, 32.3, and 43.1%, respectively. Based on the concatenated coding sequences of cp PCGs, the phylogenetic analysis showed that A. capillaris and A. selengensis are closely related to each other within the family Compositae.